STRUCTURE OF COPPER-COMPLEXES ADSORBED ON A SILICA-GEL SURFACE CHEMICALLY-MODIFIED WITH BENZIMIDAZOLE - Dias, N. L.; Gushikem, Y.; Rodrigues, E.; Moreira, J. C.; Polito, W. L. (Royal Soc Chemistry, 1994)
Silica gel having a particle size between 0.2 and 0.05 mm and a specific surface area, S(BET) = 473 M2 g-1, was chemically modified with benzimidazole. Adsorption isotherms of CuX2 (X = Cl, Br or ClO4) from ethanol and acetone solutions were studied at 298 K. The metal is bonded to the surface through the free nitrogen atom of the attached benzimidazole. The average number of ligands co-ordinated to the central metal ion was shown to depend on the solid surface loading by the solute. At low loading the electronic and ESR spectral parameters indicated that the copper ion is in a distorted-tetragonal symmetry field.